ETHNOGRAPHIC STUDY OF SONGKET WEAVERS IN SUKARARA VILLAGE - Baiq El Badriati; Nur Syam; Sirajul Arifin (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2022)
This article addresses the intersection between gender, ethnicity, work performance, and economic capital. It focuses on Sasak Muslim women who weave songkets and their economic capital in Sukarara Village, Central Lombok. This article using an ethnographic approach focused on economic capital of songket weaver. The behavior, attitudes, and personalities that are inherent in weavers in their daily operations are examined holistically and particularly through qualitative research. This study found that Sasak Muslim women who weave songket fabric in Sukarara are in good performance due to their ability to use time wisely and complete tasks quickly and effectively. They are economically capable based on a lack of consumer debt, their capacity in business, their possession of investments, their ability to manage business finances, and their mental readiness for monetary turbulence. In this framework, Sasak Muslim women’s economic capital in songket weaving is separated into three roles: as the center of the family, as vehicles for personal fulfillment, and as wives.